Faktor Penyebab Terjadi Tindak Pidana Penganiayaan Anak - Indriyanti Mahmud; Lisnawaty W. Badu; Avelia Rahmah Y. Mantali (Jurnal Hukum dan Sosial Politik, 2024)
This research aims to determine the causes of criminal acts of child abuse. This research uses empirical legal methods and is based on phenomena and realities in the field, then analyzed descriptively. The results of the research are that the causes of criminal acts of child abuse in Gorontalo consist of internal factors originating from within the child in the form of a disputed object that arises when there is a previous debate between children, whether insults or fighting over things to close friends (boyfriends), the existence of feelings of hurt that arise because of other people's actions and words to themselves which offend the feelings and inner thoughts of children who are still unstable as being childish and not thinking far ahead. Meanwhile external factors consist of lack of family supervision; Existence of Organizational Groups; Lack of Mastery of Moral and Religious Education; and Electronic Media Broadcasts.